An Effective aid program for Australia : making a real difference - delivering real results (AusAid CanberraAU, 2011)
Sets out the purpose of the Australian aid programme; the strategy for making aid more effective; the focus of the aid programme and priority regions and countries for access to Australian aid.
Keywords: DEVELOPMENT AID